Dry-Wet Cycles Affect Nitrous Oxide Emissions Across Aquatic-Terrestrial Interfaces: A Mesocosms Study - Pinto, Renata; Weigelhofer, Gabriele; Pucher, Matthias; Hood-Nowotny, Rebecca Clare; Bonin, Patricia; Brito, António Guerreiro; Hein, Thomas (Frontiers in Soil Science, 2022)
Aquatic-terrestrial interfaces may act as biogeochemical hotspots for greenhouse gas emissions, especially when exposed to frequent transitions between wet and dry phases. The study aimed to analyze the dynamics of nitrogen (N) processing along an inundation gradient from floodplain soils to river sediments and identify environmental factors affecting net nitrous oxide (N2O) production from different microbial sources. Intact soil and sediment cores were subject to two consecutive drying-rewetting cycles in laboratory experiments. The 15N isotope pairing technique was used to quantify N2O emissions sourced from denitrification and nitrification. We observed enhanced N2O emissions from both nitrification and denitrification following drying events. Sites exposed to frequent drying-rewetting cycles appear less affected by drying than hydrologically more stable habitats. Fluxes from nitrification were related to the organic matter content, while fluxes from denitrification were controlled by dissolved organic matter quality changes during the drying-rewetting cycles. This study shows the potential link between carbon metabolism and N2O production, combining the effect of drying-rewetting cycles.